New bispecific antibodies in diffuse large B-cell lymphoma - Adrian G. Minson; Michael J. Dickinson (Haematologica)
The CD20xCD3 T-cell-engaging bispecific antibodies are a highly active new treatment option for patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Epcoritamab and glofitamab have both been approved in over thirty countries as monotherapy for DLBCL after two prior treatment lines; odronextamab has recent European approval, and mosunetuzumab is active and is being developed as a combination partner. These agents can be safely combined with other immunotherapies and chemotherapy, and single-arm and randomised trial outcomes promise an expanding role for this class of drugs in earlier treatment lines. This review examines the clinical development of the CD20xCD3 bispecific antibodies in DLBCL, how the phase I and II trials inform their current use, and the key distinctions between the agents. We focus on the efficacy and safety of those bispecific antibodies most advanced in development. We also consider emerging understandings of resistance mechanisms. Finally, we review key ongoing trials and combinations and consider the potential future of bispecific antibodies within the sequence of available treatments for DLBCL.